1999
DOI: 10.1136/gut.44.5.653
|View full text |Cite
|
Sign up to set email alerts
|

Bovine colostrum is a health food supplement which prevents NSAID induced gut damage

Abstract: Background-Non-steroidal anti-inflammatory drugs (NSAIDs) are eVective for arthritis but cause gastrointestinal injury. Bovine colostrum is a rich source of growth factors and is marketed as a health food supplement. Aims-To examine whether spray dried, defatted colostrum or milk preparations could reduce gastrointestinal injury caused by indomethacin. Methods-EVects of test solutions, administered orally, were examined using an indomethacin restraint rat model of gastric damage and an indomethacin mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
127
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(137 citation statements)
references
References 23 publications
6
127
0
1
Order By: Relevance
“…Adding colostrum in the starter diet of weaned piglets resulted in numerically higher SI relative weight and duodenal villous height, indicating that colostrum may stimulate mucosa growth as it has already been demonstrated in rodents [3]. Authors have also described a colostrum-induced enhancement of cell proliferation and migration using in vitro human colonic carcinoma cells and rat SI epithelial cell models of wound repair [3]. Our results in vivo did not confirm these latter observations since any significant variation in crypt cell proliferation and migration was explained by the colostrum treatment.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Adding colostrum in the starter diet of weaned piglets resulted in numerically higher SI relative weight and duodenal villous height, indicating that colostrum may stimulate mucosa growth as it has already been demonstrated in rodents [3]. Authors have also described a colostrum-induced enhancement of cell proliferation and migration using in vitro human colonic carcinoma cells and rat SI epithelial cell models of wound repair [3]. Our results in vivo did not confirm these latter observations since any significant variation in crypt cell proliferation and migration was explained by the colostrum treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore suckling piglets were compared with weaned piglets fed a colostrum-supplemented diet in order to evaluate colostrum-induced improvement of weaning transition from digestive physiological aspects. Adding colostrum in the starter diet of weaned piglets resulted in numerically higher SI relative weight and duodenal villous height, indicating that colostrum may stimulate mucosa growth as it has already been demonstrated in rodents [3]. Authors have also described a colostrum-induced enhancement of cell proliferation and migration using in vitro human colonic carcinoma cells and rat SI epithelial cell models of wound repair [3].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…BC has been shown to prevent induced villous atrophy in mice (31) and stimulate mucosal healing in patients suffering from inflammatory gut diseases (17). BC also protects the intestinal mucosa from bacterial adhesion (29) and reduces diarrhea in infants (35).…”
mentioning
confidence: 99%
“…It has recently been shown that BC inhibits nuclear factor-B-mediated proinflammatory cytokine expression in intestinal epithelial cells (1), which may be clinically relevant as nuclear factor-B has a pivotal role in the development of NEC (7). BC is a commercially available coproduct of the dairy industry, and current farming methods allow for production of large volumes of BC for clinical use (13,31).…”
mentioning
confidence: 99%